Role of 5-HT1A and 5-HT7 Receptors in Memory Regulation and the Importance of Their Coexpression: A Systematic Review - Alfredo Briones-Aranda; Daniela Flores-Durán; Rodrigo Romero-Nava; Josselin Carolina Corzo-Gómez; Refugio Cruz-Trujillo; Floribert Toalá-Sepúlveda; Blanca E. Del-Río-Navarro; Fengyang Huang (Biomolecules)
The 5-HT1A and 5-HT7 receptors play a key role in regulating cognitive processes and have been widely linked to the pathophysiology of depression, anxiety, and schizophrenia—disorders often associated with memory impairment. Recently, interest has grown in understanding how the coexpression of these receptors contributes to cognitive decline. This review explores the individual roles of 5-HT1A and 5-HT7 receptors, as well as their coexpression, in memory regulation. The heterodimerization of these receptors at both pre- and postsynaptic levels, along with their colocalization in serotonergic, glutamatergic, GABAergic, and dopaminergic neurons, adds to the complexity of this interaction and may help explain the paradoxical effects of selective serotonergic drugs (agonists and antagonists). These findings underscore the need for further research into the 5-HT1A and 5-HT7 receptor relationship in cognitive decline through diverse approaches, including targeted gene silencing, electrophysiology, and cell culture studies.